EFL Teachers’ Voice about the Pedagogical Competencies in Teaching English Grammar Context - Hustiana Hustiana; Asdar Asdar; Ahyadi Ahyadi (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
This research was focused on understanding pedagogical competence voiced by EFL teachers in teaching grammar context. The research was conducted in Makassar. This study was descriptive qualitative research that involved six teachers in Makassar as participants which chose randomly. The instrument of this research was an interview which was analyzed with a qualitative method. The result of the current study showed that four indicators including pedagogical competence owned by the teachers namely the competence in understanding the students’ need in learning grammar, competence in preparing teaching grammar, competence in choosing method and technique in teaching grammar, and competence in choosing assignment and evaluating the students’ outcome after learning grammar. This research would have a great theoretical and practical contribution to undergraduate students and future researchers in the English language department, especially students from the education department or candidates of teachers in terms of understanding pedagogical competence.